2016
DOI: 10.17511/ijmrr.2016.i09.26
|View full text |Cite
|
Sign up to set email alerts
|

Study on various congenital anomalies in fetal autopsy

Abstract: Introduction: The study of dead is to save the livings. Congenital malformations have become important cause of fetal and neonatal (perinatal) mortality in developed countries and would very soon be increasingly important determinants of fetal mortality in developing countries like India. The fetal autopsy plays the vital role in the conformation, identification of congenital anomalies and also for the counselling of the parents, to prevent the fetal congenital anomalies in further pregnancies. This study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Our study also shows similar results with neural tube defects, heart defects and renal anamolies being the predominant [12]. Some studies have also shown that congenital anamolies are common in the low birth weight babies [13].…”
Section: Discussionsupporting
confidence: 89%
“…Our study also shows similar results with neural tube defects, heart defects and renal anamolies being the predominant [12]. Some studies have also shown that congenital anamolies are common in the low birth weight babies [13].…”
Section: Discussionsupporting
confidence: 89%